A five‐gene panel refines differential diagnosis of thyroid nodules. Issue 9 (28th July 2021) - Lu, Sang‐Yu; Chen, Ying‐Chao; Zhu, Chen‐Fang; Chen, Jing; Zhou, Qin‐Yi; Zhang, Man‐Man; Zhang, Qian‐Yue; Lu, Meng; Yang, Liu; Wu, Jing; Zhao, Shuang‐Xia; Song, Huai‐Dong; et al.
Abstract: Background: Molecular testing for oncogenic mutations in fine‐needle aspiration has showed high predictive value in identifying malignant lesions from thyroid nodules with indeterminate cytology. Methods: To figure out an efficient and economical gene panel for most medical institutions in China, we designed a five‐gene panel including BRAF / NRAS / KRAS / HRAS / TERT genes and conducted a retrospective study to evaluate the role of this five‐gene diagnostic panel in differential diagnosis of thyroid nodules. Results: A total of 665 patients with 695 thyroid nodules were investigated in the current study. The fine‐needle aspiration biopsy and surgically separated thyroid tissue specimens were harvested to test BRAF, TERT, NRAS, KRAS, and HRAS mutations. We identified 261 mutations in 665 patients, including 177 V600E mutations in BRAF . Three hundred and sixty‐nine patients who underwent thyroid surgery after completion of the initial clinical and cytological evaluation were enrolled in the final analysis. The diagnostic sensitivity, specificity, and accuracy of the combination of FNAB cytology and five‐gene detection were 74.7%, 93.8%, and 84.8%, respectively. BRAF V600E and five‐gene panel could recognize 46.4% and 53.6% of papillary thyroid carcinoma in the patients with cytologically indeterminate nodules. Conclusion: The five‐gene panel can effectively improve the sensitivity, negative predictive value, and accuracy of fine‐needle aspiration biopsy cytology, especially in the patients with cytologically indeterminate nodules. Abstract : Our study focuses on the feasibility and utility of a five‐gene panel containing BRAF / RAS / TERT mutation detection in the improvement of fine‐needle aspiration biopsy (FNAB) cytology in differential diagnosis of thyroid nodules in China. Our results demonstrated that BRAF /five‐gene mutations detected in FNAB samples can effectively improve the sensitivity, negative predictive value (NPV), and accuracy of FNAB cytology, while kept the specificity and positive predictive value (PPV).